Cross-cultural management: essential insights for international marketers - Holden, Nigel; Glisby, Martin (Henry Stewart Talks, 2009)
Culture is a major variable in the planning and execution of international marketing programs, The traditional values-based assumptions about culture have limitations in today's interconnected global economy, An alternative concept focuses on international marketing as a knowledge-based activity, Examples of challenges and benefits of this approach